Exploring the role of temperature in observed inter-population differences of Atlantic cod (Gadus morhua) growth with a 4-dimensional modelling approach. (1st April 2021) - Sokolova, Nadezhda; Butzin, Martin; Dahlke, Flemming; Werner, Karl Michael; Balting, Daniel; Lohmann, Gerrit; Pörtner, Hans-Otto
Abstract: Atlantic cod ( Gadus morhua ) is one of the most commercially important fish species in the North Atlantic. Environmental factors, such as water temperatures, influence growth of individuals over time, thus forming population-specific growth patterns across climatic regions. Here we develop an integrative approach to investigate the role of temperature in shaping geographic differences of cod growth in the Celtic Sea, North Sea, Iceland, and Barents Sea. We combine a physiology-based growth model and 50-years observational temperature data of 0.5 × 0.5° spatial resolution to simulate continuous growth of cod. The model generated weight-at-age data for the period 1959–2007 which we compared to observational data from fishery-independent scientific surveys. In the Celtic and the northern North Sea, simulated growth matches well observational data. We also show that relatively warm temperatures in the Celtic Sea facilitate maximum growth rates; future warming is likely to have a negative impact on growth of these cod stocks. Growth simulations in Icelandic waters and the Barents Sea are less consistent with local observational data. More complex growth patterns in these regions are probably shaped by ontogenetic shifts in temperature regimes, feeding conditions and physiological adaptations. These findings should stimulate further research on critical processes to be considered in population-specific projections of growth of cod and productivity.